Standardized Comparison of Selected Physiological Controllers for Rotary Blood Pumps: In Vitro Study. Issue 3 (2nd November 2017) - Petrou, Anastasios; Lee, Jongseok; Dual, Seraina; Ochsner, Gregor; Meboldt, Mirko; Schmid Daners, Marianne
Abstract: Various physiological controllers for left ventricular assist devices (LVADs) have been developed to prevent flow conditions that may lead to left ventricular (LV) suction and overload. In the current study, we selected and implemented six of the most promising physiological controllers presented in literature. We tuned the controllers for the same objectives by using the loop‐shaping method from control theory. The in vitro experiments were derived from literature and included different preload, afterload, and contractility variations. All experiments were repeated with an increased or decreased contractility from the baseline pathological circulation and with simulated sensor drift. The controller performances were compared with an LVAD operated at constant speed (CS) and a physiological circulation. During preload variations, all controllers resulted in a pump flow change that resembled the cardiac output response of the physiological circulation. For afterload variations, the response varied among the controllers, whereas some of them presented a high sensitivity to contractility or sensor drift, leading to LV suction and overload. In such cases, the need for recalibration of the controllers or the sensor is indicated. Preload‐based physiological controllers showed their clinical significance by outperforming the CS operation and promise many benefits for the LVAD therapy. However, their clinical implementation in the near future for long‐term use is highly dependent on the sensor technology and its reliability.